IOT-Based Home Security Using Magnetic Sensor - Nurfiana Nurfiana; Andri Efendi; Retno Dwi Handayani (Proceeding International Conference on Information Technology and Business, 2020)
Security was very important, particularly in home security, because the house was a place to live and to store the valuable goods. The crime rate (e.g., theft) increases as homeowners left the house empty. They who wanted to travel and leave the house empty for along time needed their house to be safe. The Internet of Things (IoT) enabled the devices to communicate (e.g., sending and receiving data). The objective of this study was designing the home door security system consisting of Node Mcu ESP 8266, VC0706 camera, magnet sensors, and speakers. The telegram application was able to provide quick information to users so that they were able to find out the situation of the house door from the theft. When the door was forcibly opened, the magnet sensor sent information to node Mcu. The node Mcu ordered the camera to take a picture and it was sent to the homeowner's smartphone through the telegram application.Keywords: Node Mcu ESP8266, Camera VC0706, Telegram Application